Jakarta Asian Games men's 20km walking championship and runnerup comparative study of technologies - Feng, X.-D.; Hu, G.-S.; Li, H.-L.; Yuan, J.; Wang, H.; Chen, Z.-B.; Yang, T.-Y. (DEStech Transactions on Social Science, Education and Human Science, 2020)
As a competitive event in China, the walking race not only carries the task of vying for gold for the country in international large-scale events such as the Olympic Games and the World Championships, but also bears the responsibility to strengthen the people's physique and drive the people's enthusiasm for sports. It also reflects to a certain extent the important symbol of the development of a sports power into a sports power. Walking race is a technology-oriented endurance event. On the basis of good endurance, it is also subject to many rules and technical constraints, which also makes it difficult for athletes to obtain good results. With the development of competitive sports, men`s 20km race walking is very fierce nowadays. The rise of Japan can be said to pose a direct threat to our men`s 20km race walking. We can see that Japan`s grasp of the key technologies of walking race is very in place, focusing on technology Details play a key role in improving athletic performance. In this paper, a comparative study of Kaihua Wang and Toshikazu Yamanishi, men of 20 kilometers from the Asian Games in Jakarta, is conducted by means of literature data analysis, image analysis, mathematical statistics and comparative analysis. The research shows that Kaihua Wang has a relatively large stride when walking at high and low speeds, but Kaihua Wang has uneven steps on the left and right. Although Kaihua Wang has a greater distance between the back pedal and the forward swing than Shanxi, he has an uneven force on the left and right legs. It is stronger than Shanxi Lihe and balance ability; when swinging at high and low speeds, the amplitude of upper limb swing is small, and the left and right are not balanced; Toshikazu Yamanishi and Hou Yi phenomenon are larger than Kaihua Wang, and when landing, Kaihua Wang has a small landing angle on the left and a large undulation distance on the head when supporting on the left.